2019
DOI: 10.1155/2019/4536268
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of CuO on the Thermal Behavior of the High-Energy Combustion Agent of the Al/MnO2 System

Abstract: In this work, the effect of CuO addition into the high-energy combustion agent of Al/MnO 2 system was studied. First, the combustion experiments of five samples with different contents had been carried out, in which CuO was found capable of influencing the flame ejection to a great extent. en, in order to find out the underlying reasons, CuO effects on the thermal behavior of Al/MnO 2 system were analyzed via theoretical calculations of Gibbs free energy and enthalpy changes. In addition, field emission scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Its average step‐up rate was 28.29 MPa/s, much higher than 6.84 MPa/s of Al/Fe 2 O 3 /CuO. Wang [28] studied the effect of CuO addition on the Al/MnO 2 thermite system and found that adding CuO would lead to a sharp increase in gas content in the whole reaction process, accompanied by rise in reaction pressure. Adding an appropriate amount of CuO was beneficial to the continuous progress of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Its average step‐up rate was 28.29 MPa/s, much higher than 6.84 MPa/s of Al/Fe 2 O 3 /CuO. Wang [28] studied the effect of CuO addition on the Al/MnO 2 thermite system and found that adding CuO would lead to a sharp increase in gas content in the whole reaction process, accompanied by rise in reaction pressure. Adding an appropriate amount of CuO was beneficial to the continuous progress of the reaction.…”
Section: Introductionmentioning
confidence: 99%